Classification of Legal Judgement Summary using Conditional Random Field Algorithm - Santhana Megala, S (International Journal of Computer Sciences and Engineering, 2025)
An Automatic Summary generation process creates a shortened version of the text using a Digital programming Technology, with the aim of holding the most advanced important points of the original text. In a Common Law system, previous judgments were referred to the current case arguments as well as decision making. Thus there is a need to view the previous judgments and to grasp and analyze the important points present in the legal judgments. Text Summarization technique helps the legal experts to read the key points present in a judgment just by reading the Head note generated by the system. Such techniques save the time as well as the manpower. In this paper, an automatic Legal Judgment Summarization system was implemented and tested by Fuzzy Logic, Classification and Segmentation techniques among that based on the experimental study Fuzzy Logic and Conditional Random Field Algorithm produces a meaningful summary.